Penerapan model pembelajaran inkuiri terbimbing untuk meningkatkan pemahaman konsep keanekaragaman hayati dalam pembelajaran IPAS - Paramitha, Catherine Dyah; Poerwanti, Jenny Indrastoeti Siti (Didaktika Dwija Indria, 2026)
This study aims to determine the application of the guided inquiry learning model to improve students' understanding of biodiversity concepts in Grade V in Science and Social Studies (IPAS) lessons at Tirtoyoso State Elementary School in Surakarta. This research method used a classroom action research design conducted in two cycles, with each cycle consisting of two meetings. The research subjects were 21 fifth-grade students at Tirtoyoso Surakarta Public Elementary School in the 2024/2025 academic year. Data were collected through observation, documentation, interviews, and tests. This study consisted of four stages: planning, implementation, observation, and reflection. The results showed a significant increase in students' understanding of biodiversity concepts. The average score in cycle 1 increased to 71.19 with a classical mastery level of 61.90%. In cycle 2, the average score increased to 81.19 with a classical mastery level of 85.71%. These results indicate that the guided inquiry learning model is effective in improving students' conceptual understanding because it transforms the learning process into an active and student-centered one, where students are directly involved in the discovery process.